2017
DOI: 10.18203/2320-1770.ijrcog20171008
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of vaginal misoprostol and intra cervical Foley’s catheter for pre-induction cervical ripening at term

Abstract: Background: At times of unfavorable cervix induction of labor with cervical ripening agents were necessary. The present study was done to compare the efficacy and outcome of vaginal misoprostol and Foleys catheter in pregnant women for induction of labor.Methods: This randomized clinical trial was performed on 10o pregnant women during a time period of December 2014 to November 2016. These women were randomly divided into two groups: Misoprostol (50 patients) and Foley catheter (50 patients). For the first gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…In the present study, the Bishop score increase in the EASI group was significantly greater than that in the other 2 groups. Contrary to this finding, some studies reported that the Bishop score increase in the misoprostol group was greater than that in either the EASI or laminaria group [9,11,16]. An explanation for this contradiction is the difference among the studies regarding misoprostol dosages.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In the present study, the Bishop score increase in the EASI group was significantly greater than that in the other 2 groups. Contrary to this finding, some studies reported that the Bishop score increase in the misoprostol group was greater than that in either the EASI or laminaria group [9,11,16]. An explanation for this contradiction is the difference among the studies regarding misoprostol dosages.…”
Section: Discussionmentioning
confidence: 81%
“…The higher rate of cesarean sections in the misoprostol group is attributable to the fact that misoprostol can cause uterine hypertonicity and, thereby, increase the risk of fetal distress and the need for emergency cesarean sections. However, some studies reported lower rates of cesarean sections in the misoprostol group than in the EASI group [7,16], and some studies found no significant difference between the misoprostol and the EASI groups regarding the rates of cesarean sections [11,12,14]. The difference among the studies regarding the rates of cesarean sections in the misoprostol, EASI, and laminaria groups may be due to the differences in the therapeutic protocols in different settings.…”
Section: Discussionmentioning
confidence: 99%
“…This study is in contrast to a study by Agarwal et al, that observed 70% of the Foley's catheter and 50% of misoprostol group were primigravida. 10 In a study by Noor et al 31.8% women of Foley's catheter and 41.7% women of misoprostol group were primigravida. 11 Most of the pregnant women in both the groups presented before their expected date at the time of recruitment.…”
Section: Discussionmentioning
confidence: 95%
“…If spontaneous expulsion of Foley's catheter did not occur till 12 hours then catheter was deflated and removed at the end of 12 hours and Bishop score was assessed. 3 Patients with cardiovascular disease, bronchial asthma, renal or hepatic disorders. Cephalopelvic disproportion, low lying placenta, acute local cervical lesion and previous lower segment caesarean section or any scar over the uterus were excluded from study.…”
Section: Methodsmentioning
confidence: 99%
“…It induces labor through direct mechanical dilation of the cervix and by stimulating the endogenous release of prostaglandins. 3 Present study is to evaluate the efficacy of Misoprostol as a cervical ripening agent and its comparison against Foley's catheter in terms of success rate, safety, side effects and patient compliance.…”
Section: Introductionmentioning
confidence: 99%